PHENOMENON OF DEMIKHOV. In the Sklifosovsky Institute (1960–1986). Scientifc Revolution in Transplantation (1960–1964). Achievements of the USA and the USSR in the feld of transplantation and transplant immunity (1962) - S. P. Glyantsev (Трансплантология (Москва), 2019)
Correspondence to: Sergey P. Glyantsev, Prof., Dr. Med. Sci., Head of the Department of the History of Cardiovascular Surgery at A.N. Bakoulev National Medical Research Center for Cardiovascular Surgery, Head of the Medical History Unit within the Medical History Department at N.A. Semashko National Research Institute of Public Health, e-mail: spglyantsev@mail.ru Received: August 08, 2018 Accepted for publication: September 12, 2018 The article presents the evidence of a scientific revolution in transplantology that occurred in the world in 1960-1964 with the shift of the paradigm from the impossibility of homoplastic organ transplants to the hope on their feasibility. It began in 1960 with awarding the Nobel Prize to P. Medawar and F. Burnet for the discovery of artificial immunological tolerance, it had its continuation in 1961–1962 with the advances in experimental transplantation of vital organs undertaken in conditions of mechanical circulation (R. Lower, N. Shumway) and immunosuppression (K. Reemstma), and completed with human transplantations of lung in 1963 and of heart in 1964 (J. Hardy). In those years, the concept of mechanical support for an ill heart by using an implanted mechanical assist device was developed and introduced (1963). But even against that background, V.P. Demikhov's achievements in homologous organ transplantation and the development of biological techniques to overcome tissue incompatibility looked impressive. His highest achievement was the transplantation of a supplemental heart to the dog Grishka in June 1962, and the dog survived with it for 141 days. However, after the discoveries in the field of transplantation immunity, the train of experimental transplantation where V.P. Demikhov was riding, began picking up speed very quickly, and the Soviet surgeons were to jump on its footboard.